LEARN TO SPEAK ENGLISH SOFTWARE THE PERSPECTIVE AND RESPONSE (AN EXPERIMENTAL STUDY AT POLITEKNIK LP3I MAKASSAR) - Trista Udin, Imran (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The objectives of this research were: to find out whether) to find out whether or not the students are interested in joining the speaking class through Learn to Speak English software. This research employed Quasi Experimental design. The sample consisted of 32 students of third semester of business administration, Politeknik LP3I Makassar in academic year 2019/2020. The data were collected through and data on the students’ interest were analyzed using Likert scale, the results of the research were: the use of Learn to Speak English software increased the students’ interest in joining the speaking class, it can be concluded the students have high interest and active toward teaching speaking through Learn to Speak English software.